John Donne and the Protestant Reformation New Perspectives - Papazian, Mary Arshagouni (Wayne State University Press, 2003)
"This collection includes thirteen essays that together place Donne broadly in the context of English and European traditions and explore his divine poetry, his prose work, the Devotions Upon Emergent Occassions, and his sermons. It becomes clear that in adopting the values of the Reformation, Donne does not completely reject everything from his Catholic background. Rather, the clash of religion erupts in his work in both moving and disconcerting ways." "This collection offers a fresh understanding of Donne's hard-won irenicism, which he achieved at great personal and professional risk."–Jacket.
Book Title: John Donne and the Protestant Reformation new perspectives, John Donne and the Protestant Reformation : new perspectives Place: Detroit, Mich.
Keywords: 17th century; Christian literature; English; 17th century; Protestantism and literature; Donne; John; 1572-1631; England; History; History and criticism; Reformation; Religion; Christianity and literature; dept.pres; faculty_collection